The Role of Organizational Flexibility in Achieving Organizational Prosperity: Field Research in a Sample of Iraqi Cellular Communications Companies - عمير عراك عبود (Journal of Economics and Administrative Sciences, 2019)
This research amid to measure the impact of organizational flexibility (structural flexibility, operational flexibility, and strategic flexibility) in achieving organizational prosperity and its dimensions (strategic agility, intellectual capital, innovation and sustainable competitive advantage) in a number of Iraqi cellular communications companies. The research adopted descriptive analytical approach. A sample of (85) persons from the research community was selected, which included (Department managers, Directors administrative units, Communication engineers), to answer the questionnaire prepared for this purpose. And to analyze data and derive results. Statistical methods were used that included mean, standard deviation, correlation analysis, and simple linear regression analysis. The results of the study showed a significant positive correlation between the organizational flexibility and their diminutions in organizational prosperity and its diminutions, and the relationship of positive effect between organizational flexibility and its diminutions in the organizational prosperity and its dimensions in the organizations studied. Based on this results of this research, it can be inferred that organizational flexibility contribute to organizational prosperity and Reflected in it.